Enhancing Vocational High School Students’ Descriptive Writing through Personal Journal Writing: An Experimental Study in an Indonesian Efl Classroom - Alfi Khairiyah; Wariyati Wariyati; Nazriani Lubis; Nurlaili Nurlaili (Universitas Palangka Raya, 2026)
Writing ability is a crucial skill in English as a Foreign Language (EFL) learning; however, many vocational high school students still experience difficulties in developing ideas, organizing texts, using appropriate vocabulary, and applying grammatical structures in descriptive writing. This study aimed to investigate the effect of Personal Journal Writing on vocational high school students’ descriptive writing achievement and to examine its contribution to students’ ability to organize ideas, use vocabulary, and apply grammatical structures. This research employed a quantitative approach using a quasi-experimental pre-test–post-test control group design. The participants were 50 eleventh-grade students at SMK Al Azmi Seidadap, North Sumatra, Indonesia, consisting of an experimental group and a control group, each comprising 25 students. Data were collected through descriptive writing tests and analyzed using descriptive statistics, Shapiro–Wilk normality test, Levene’s test, and an independent-samples t-test using IBM SPSS Statistics. The results revealed that the experimental group showed a higher improvement in writing achievement, with the mean score increasing from 59.88 in the pre-test to 81.96 in the post-test, while the control group improved from 59.84 to 66.84. The independent-samples t-test indicated a statistically significant difference between the two groups (t(48) = 9.376, p < .001). These findings demonstrate that Personal Journal Writing significantly improves students’ descriptive writing ability by supporting idea development, vocabulary enrichment, text organization, and grammatical accuracy. Therefore, Personal Journal Writing is recommended as an effective learner-centered strategy for enhancing EFL writing instruction in vocational high schools.